A survey-based assessment of rates and covariates of mpox diagnosis and vaccination provides evidence to refine eligibility criteria for mpox vaccination among gay, bisexual and other men who have sex with men in the Netherlands - Adam, Philippe C. G.; Op de Coul, Eline L. M.; Zantkuijl, Paul; Xiridou, Maria; Bos, Hanna; Blom, Cor; Ketsuwan, Itsada; te Wierik, Margreet J. M.; David, Silke; de Wit, John B. F. (Frontiers in Public Health, 2024)
Background: The 2022 multicountry mpox outbreaks predominantly affected gay, bisexual and other men who have sex with men (GBMSM) in non-endemic countries, including the Netherlands. We conducted a survey-based assessment of the alignment between the risk factors associated with mpox diagnosis among GBMSM in the Netherlands and the eligibility criteria used in 2022 for vaccinating this group, with the aim to refine these criteria.Methods: An online self-report survey was conducted among adult GBMSM in the Netherlands between 29 July and 30 August 30, 2022, corresponding to the first month of the Dutch mpox vaccination campaign. GBMSM were recruited via advertisements on social media and gay dating apps. Participants reported on their sexual behaviour, mpox diagnosis, and/or (initial) mpox vaccination since the start of the outbreak. Covariables of mpox diagnosis and vaccination were assessed using logistic regression analyses.Results: Of the 2,460 participants, 73 (3.0%, 95% CI 2.3%-3.6%) were diagnosed with mpox and 485 (19.7% , 95% CI 18.1%-21.3%) had received (initial) mpox vaccination.Using sample weighting, we estimated that, of the GBMSM population aged 18-80 years in the Netherlands, 1.1% (95% CI 0.7% -1.6%) had been diagnosed with mpox and 7.8% (95% CI 6.8%-8.9%) had received (initial) vaccination. HIV-PrEP use, living with HIV, reporting ³20 sex partners in the past 12 months, and sex in sex venues/parties in the past 2 months were independent risk factors for mpox diagnosis. Except for sex in sex venues/parties, these variables were also independently associated with mpox vaccination.This study provides novel evidence regarding the degree to which the 2022 eligibility criteria for mpox vaccination align with the risk factors for mpox among GBMSM in the Netherlands. The findings contribute to a refinement of the eligibility criteria for mpox vaccination, to which sex in sex venues/parties should be added.